2001
DOI: 10.1136/jnnp.71.6.798
|View full text |Cite
|
Sign up to set email alerts
|

Infundibulohypophysitis in a man presenting with diabetes insipidus and cavernous sinus involvement

Abstract: Infundibulohypophysitis is an unusual inflammatory condition that aVects the infundibulum, the pituitary stalk, and the neurohypophysis and may be part of a range that includes lymphocytic hypophysitis. Lymphocytic hypophysitis occurs mainly in women and most often presents in the later stages of pregnancy. Infundibulohypophysitis usually presents with diabetes insipidus and the cause remains unclear. The case of a 46 year old man with a 12 week history of polyuria and polydipsia is reported. Cranial diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…Typically, this disease occurs in young women in late pregnancy or in the postpartum period (2). However, there have been some recent reports of men presenting with lymphocytic hypophysitis (8)(9)(10). Previously, distinctions were made between lymphocytic hypophysitis and lymphocytic infundibulohypophysitis.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, this disease occurs in young women in late pregnancy or in the postpartum period (2). However, there have been some recent reports of men presenting with lymphocytic hypophysitis (8)(9)(10). Previously, distinctions were made between lymphocytic hypophysitis and lymphocytic infundibulohypophysitis.…”
Section: Discussionmentioning
confidence: 99%
“…41 Therefore, the parasellar T2 dark sign is more suitable for LYH that infiltrates around the pituitary. Some previous studies have reported cavernous involvement in patients with LYH, 5,6,10,[42][43][44][45][46] but no studies have mentioned the parasellar T2 dark sign.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported satisfactory responses to high dose steroid therapy and methotrexate injection [5,9,16,18,19]. The diagnosis of all cases was lymphocytic hypophysitis.…”
Section: Managementmentioning
confidence: 97%